Discourse, Peace, and Conflict Discursive Psychology Perspectives (Peace Psychology Book Series, 2018)
This first-of-its-kind volume brings discursive psychology and peace psychology together in a compelling practical synthesis. An array of internationally-recognised contributors examine multiple dimensions of discourse-official and casual, speech, rhetoric, and text-in creating and maintaining conflict and building mediation and reconciliation. Examples of strategies for dealing with longstanding conflicts (the Middle East), significant flashpoints (the Charlie Hebdo case), and current heated disputes (the refugee 'crisis' in Europe) demonstrate discursive methods in context as they bridge theory with real life. This diversity of subject matter is matched by the range of discursive approaches applied to peace psychology concepts, methods, and practice. Among the topics covered: Discursive approaches to violence against women. The American gun control debate: a discursive analysis. Constructing peace and violence in the Palestinian-Israeli conflict. Discursive psychological research on refugees. Citizenship, social injustice, and the quest for a critical social psychology of peace. The emotional and political power of images of suffering: discursive psychology and the study of visual rhetoric. Discourse, Peace, and Conflict offers expansive ideas to scholars and practitioners in peace psychology, as well as those in related areas such as social psychology, political psychology, and community psychology with an interest in issues pertaining to peace and conflict.